Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian The Sandal’s Di Tanah Abang - Azzahra, Sheris; As'ad, Muhammad (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The intense competition in the footwear industry in Tanah Abang requires producers to understand the factors that influence consumer purchasing decisions, particularly price and product quality. This research aims to examine and analyze the influence of price and product quality on the purchasing decisions of The Sandal’s consumers in Tanah Abang. A quantitative approach was applied using multiple linear regression analysis processed through SPSS version 24. The results show that price has a positive and significant partial influence on purchase decisions, contributing 66.9%. Product quality has an even stronger influence, contributing 71.0%. Simultaneously, price and product quality have a significant effect on purchase decisions, with a coefficient of determination (R ²) of 76.8%. These findings suggest that improving product quality and implementing appropriate pricing strategies are essential to increasing purchase decisions for The Sandal’s in Tanah Abang.